Relationship between monsoon onset over Thiruvananthapuram and Mumbai and rainfall over Kerala and Konkan - SHEWALE , M. P.; PONKSHE, A. S. (MAUSAM, 2006)
Lkkj & bl ’kks/k&Ik= esa nks LFkkuksa uker% fFk:ouUriqje vkSj eqEcbZ dk p;u djds ;g irk yxkus dk iz;kl fd;k x;k gS fd D;k ekulwu ds vkxeu dh rkjh[k dk Øze’k% dsjy vkSj dksad.k esa gksus okyh o"kkZ ds lkFk dksbZ laca/k gS A lewps ns’k ds fy, Hkkjrh; xzh"edkyhu ekulwu o"kkZ ¼vkbZ- ,l- ,e- vkj-½ ds lkFk ekulwu ds vkxeu dh rkjh[k ds laca/k dh Hkh tk¡p dh xbZ gS A bl v/;;u ds fy, 100 o"kksaZ ¼1901&2000½ ds vk¡dM+ksa dk mi;ksx fd;k x;k gS A fo’ys"k.k dh lgk;rk ls vk¡dM+ksa dh ,d:irk vkSj o"kkZ ds vU; yk.kksa dh tk¡p dh xbZ gS A dsjy vkSj dksad.k esa vdky vkSj ekSle laca/kh ck<+ dh ledkfyd ?kVukvksa dh vko`fr dk irk yxk;k x;k gS vkSj mldh tk¡p dh xbZ gS A bl v/;;u ls ;g irk pyk gS fd ekulwu ds vkxeu ds laca/k esa fFk:ouUriqje vkSj eqEcbZ ds chp egRoiw.kZ laca/k gS A fFk:ouariqje vFkok eqEcbZ vkSj vkbZ- ,l- ,u- vkj- ds chp ekulwu ds vkxeu ds ckjs esa fdlh egRoiw.kZ laca/k dk irk ugha pyk gS A dsjy dh rqyuk eas dksad.k esa ekSle laca/kh ck<+ vf/kd vkrh gS A In this paper, choosing two locations viz., Thiruvananthapuram and Mumbai, an attempt has been made to find whether the onset date of monsoon has any bearing on monsoon rainfall over Kerala and Konkan respectively. Association of the onset dates with Indian Summer Monsoon Rainfall (ISMR) for the country as a whole has also been explored. The study utilizes 100 years’ (1901-2000) data. Homogeneity of the data and other rainfall features have been examined with the help of analysis. Frequency of simultaneous occurrence of droughts and meteorological floods at Kerala and Konkan have been determined and examined. The study showed that onset over Thiruvananthapuram and Mumbai are significantly related. It revealed absence of any significant relationship between onset over Thiruvananthapuram or Mumbai and the ISMR. Meteorological floods seem to be more frequent over Konkan compared to Kerala.